SmartRegio. Employing spatial data to provide decision support for SMEs and city administrations. - Memmel, Martin; Abecker, Andreas; Bretthauer, Sebastian; Kirchmann, Heinz; Korf, Roman; May, Markus; Wacker, Richard (My University, 2017)
When decisions have to be made which are based on the characteristics and expected developments in specific spatial environments (such as finding the best place for a new production site or for a new shop), geo data and the information that can be derived from it plays a crucial role. While larger companies typically can afford the setup of the required organisational units as well as the access to relevant data from commercial providers, smaller organisations such as SMEs or city administrations are at a disadvantage. The aim of the SmartRegio project was to develop solutions for such organisations that combine freely available (mass) spatial data from many different sources as a decision-making basis focusing on governmental and private actors operating with a focus on a specific region. The data sources include data from infrastructures like energy and mobility, data from public entities, and also data from social media and media channels. The SmartRegio project successfully identified and tackled major technical and legal challenges when aiming to exploit such data, while at the same time realising a generic infrastructure that supports the required processes within the given context.
Keywords: Raumdaten; Regionaldaten; Planungsdaten; Datenbeschaffung; Datensammlung; Datenanalyse; Kommunalverwaltung; KMU; Kleinunternehmen; Mittelunternehmen; Entscheidungsfindung; Datengrundlage